FC Geo-cool: earth coupled solar assisted hybrid heat pump energy efficient cooling system - Howard Miller, Alfred; Abdul Majeed, Fesmi; Alwahabi, Suhair; Abuharaz, Mazin; Midathada, Anil; Belachew, Chanyalew (International Journal of Engineering and Technology, 2019)
This applied research topic addresses the potential of integrating a Solar Power Assisted Ground Source Heat Pump, for the purpose of space cooling at HCT Fujairah Women's and Fujairah Men's College building(s), United Arab Emirates (UAE). The proposed model is designed such to provide sustainable cooling. A ground source heat pump dependent upon a heat transfer grid of four vertical drilled boreholes of 360-400 feet depth (100-125m) with closed vertical loop constructed of saltwater resistant polyethylene tubing, with thermally enhanced, Bentonite grouted construction, to protect from groundwater contamination, while promoting effective heat transfer between the earth and closed-loop tubes. The system will deploy thermoelectric generators and a nocturnal cooling radiator to dissipate heat from the closed loop. The system is expected to produce a cooling power of about 12 kW at an approximate cost of a solar assisted ground source cooling system of AED 80,000, about $22,000 USD, equipment only, system with cost-benefit analysis improved by a diligent administration, negotiation, management, and design; the system will be able to accomplish this target.Â Â